Pengelolaan Sampah Rumah Tangga Berbasis Masyarakat Perkotaan - Yusuf, Hika Legiana Wati Dwi; Melyana, Ira; Lestari, Dwinta Rachmanitta; Zahroh, Syahira Rohmatun; Fadhilah, Salma Fatin; Prambudhi, Ikhlas; Setiaputra, Rizky; Putra, Reza Fauzy Kesumo; Gumilang, Cahya Putra; Musthafa, Hafizh; Setiawan, Agus Nugroho (Universitas Muhammadiyah Yogyakarta, 2025)
Organic waste is one of the main issues in RW 11 Pandeyan Village, Umbulharjo, Yogyakarta, which requires sustainable management. If not properly managed, organic waste can lead to harmful environmental impacts, such as pollution and health problems. This community service program aims to optimize organic waste management through household-scale composting using composter bags. The community service is carried out with a participatory approach that directly involves the community. The methods used in this program include initial observation and coordination, socialization and outreach, waste processing training, composting practice, and community mentoring. Monitoring and evaluation activities are conducted to measure the program's effectiveness and identify areas for improvement. The results of the community service program show an increase in community involvement in waste management, as well as the formation of composting groups. Additionally, there has been a change in the residents' habits in managing waste, making them more independent. In the long term, it is expected that the organic waste bank management group will be strengthened, and the economic potential of compost products will be developed.